Changes in personnel policies of enterprises conditioned by the identification of knowledge workers - Igielski Michał (Management, 2015)
The twenty-first century requires enterprises to change in their functioning, since management has been faced with an unprecedented challenge so far – it is the result of a turbulent external environment. Due to transformations the companies cannot continue to build their competitive advantages based on investments in tangible resources and cheap labour. They have to turn into organizations based on knowledge, skills and competencies, which involves the use of new management methods. Therefore, the most desirable employees are those who through education, skills and experience are able to help businesses operate on the market. Companies in their strategies appreciate knowledge workers, who in the world today, in the era of endless crisis, can decide and determine gaining a competitive position in the market. We must also remember that the policy of qualification and skills of knowledge workers must arise from the strategy of personnel of the company. Therefore, the author of this article believes that it is necessary to customize personnel strategies in enterprises to the needs of knowledge employees working in them.